Exploring the Contribution of Traditional Medicinal Herbs in Managing Polycystic Ovary Syndrome: A Comprehensive Review - Mali, Abhijeet Shivshankar; Arulmozhi, S. (Current Indian Science, 2024)
Polycystic ovary syndrome (PCOS) is a significant gynecological disorder that commonly affects women of reproductive age. Disturbances in the production and metabolism of androgens and estrogens mark the condition. Due to the rising occurrence of PCOS and its related physical and psychological issues, along with the role of sex hormone fluctuations in its development, the use of marketed drugs is effective in treating PCOS but is accompanied by negative consequences. Consequently, a significant number of individuals with PCOS are opting for natural remedies due to the positive therapeutic effects associated with natural medications and the constraints of allopathic treatments. This review aims to assess the impact of different herbs on alterations in sex hormone levels in the bloodstream and ovarian tissue. By conducting a comprehensive literature search utilizing databases such as PubMed, Google Scholar, and Crossref, we have gathered and analyzed pertinent information regarding the efficacy of herbal remedies in combating PCOS. Based on the available evidence, herbs consisting of phytoestrogens can potentially reduce insulin resistance, hyperandrogenism, and ovarian weight while facilitating ovulation. This review explores the importance of herbal remedies in addressing PCOS, elucidates their mechanisms of action, and examines the therapeutic uses of specific herbal medications to treat PCOS. Human studies on medicinal herbs for managing Polycystic Ovary Syndrome (PCOS) need extended durations for a comprehensive evaluation of both safety and efficacy, emphasizing the necessity for more long-term research. It is anticipated that this comprehensive review will serve as a valuable resource for researchers studying the effect of herbs on PCOS, providing them with valuable insights and information.
Keywords: Medicinal herbs